Тheoretical and applied provisions of the research of the state budget deficit in the countries of Central and Eastern Europe - Shkarlet, S.; Dubyna, M.; Hrubliak, O.; Zhavoronok, А. (Administratie si Management Public, 2019)
Within the article, a comprehensive study of the state budget deficit in the Central and Eastern Europe (CEE) countries is presented, the effectiveness of managing it is determined. Considerable attention is paid to the deepening of methodical aspects of the assessment of trends in the formation of revenues and expenditures of the identified budgets, the algorithm for defining the deficit of the budget is detailed and it is tested in practice. The obtained results provide an opportunity to establish that the size of the state's deficit depends in part on the economic development of the state and at the same time, its existence can have a positive effect on the growth rate of the national economy. In order to establish the peculiarities of such interaction, a comparative analysis between the deficit ratio of the state budgets and the level of GDP in the CEE countries is carried out. The study confirmed the thesis on the correlation between these indicators and it was also possible to determine in the long run (2007-2017) how these parameters changed. It is established that the accelerated pace of GDP growth with simultaneous growth of the state budget deficit is an indicator of its effective management, as economic growth allows for new, unplanned revenues and other incomings that will reduce the size of the gap between revenues and expenditures of such a budget. In turn, in case of rapid growth of the deficit against the backdrop of insignificant growth rates of the country's GDP, it shows that some of the country's financial resources are spent inefficiently and are not used to stimulate economic development in the state. In this case, the funds are spent on the social sphere maintenance, raising the level of economic provision of citizens of the state. However, such processes can take place only in the short term, since the deficit itself will need to be further covered by other revenue items of the budget. Taking into consideration the outlined, it is stated in the article, that improper management of the state budget deficit may have long-term negative consequences for the functioning
Keywords: deficit, state budget, budget revenues, budget expenditures, budget deficit indicator, GDP.